Spatial Performance Evaluation of Government Center: Economic Leakage Analysis Using Multiplier Effect Method in Mojokerto Regency - Abbas, Mohammad Saichul; Wicaksono, Agus Dwi; Utomo, Dadang Meru; Munada, Wina (Civil and Environmental Science Journal (CIVENSE), 2026)
Placing a government capital in the wrong location does more than cause administrative headaches. It actively breaks the local economy. This study investigates the severe spatial mismatch in Mojokerto Regency, where its government center operates as an enclave entirely within Mojokerto City. We analyzed 2018–2023 GRDP data using Location Quotient (LQ), Shift-Share Analysis (SSA), and Keynesian Multiplier models. Our findings reveal a striking irony. The Regency’s bureaucracy actually functions as a basic sector for the neighboring City while remaining non-basic for its own territory. The SSA results prove this damage. Local tertiary sectors suffer heavy competitive losses because they miss out on the daily spending of civil servants. This enclave setup triggers massive economic leakage. Money drains out through direct office procurement and indirect daily consumption, creating a textbook backwash effect. Beyond lost revenue, this mismatch forces unsustainable daily commutes that heavily spike the region's carbon footprint. We conclude that relocating the government hub into the Regency’s actual borders is an urgent economic necessity, not just a political option. Until this physical relocation happens, local planners must consider cross-border revenue-sharing to stop the immediate financial bleeding.